2000
DOI: 10.1149/1.1393622
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Low-Temperature Performance of Li-Ion Cells

Abstract: Li-ion batteries are widely used at room temperature because of their high specific energy and energy density, long cycle life, low self-discharge, and long shelf life. 1-3 For certain defense and space applications they are required to be used at low temperatures (<Ϫ30ЊC). In general they exhibit poor low-temperature performance. For example, it has been reported that the capacity of Li-ion cells at Ϫ40ЊC is 12% of the room temperature value. 4 It has been suggested that the poor performance of Li-ion batteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
216
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(223 citation statements)
references
References 8 publications
6
216
0
1
Order By: Relevance
“…The delivered capacities of the cell reached 143 mAh g À 1 at 30°C, 147.6 mAh g À 1 at 55°C and 128.8 mAh g À 1 at 0°C. The capacity decreases to 114 mAh g À 1 at À 20°C; however, this value is still sufficiently high compared with Li cells [45][46][47] . At 30°C, the average operation voltage is found to be 2.84 V on discharge.…”
Section: Discussionmentioning
confidence: 90%
“…The delivered capacities of the cell reached 143 mAh g À 1 at 30°C, 147.6 mAh g À 1 at 55°C and 128.8 mAh g À 1 at 0°C. The capacity decreases to 114 mAh g À 1 at À 20°C; however, this value is still sufficiently high compared with Li cells [45][46][47] . At 30°C, the average operation voltage is found to be 2.84 V on discharge.…”
Section: Discussionmentioning
confidence: 90%
“…Huang et al [80] and Lin et al [76] pointed out that a lithium-ion battery might be able to be discharged normally at low temperatures, but not so during reverse charging process. Nagasubramanian [81] reported that the commercial 18650 lithium-ion battery has only 5% of energy density and 1.25% of power density compared to that obtained at 20°C.…”
Section: Sub-zero Temperature Performancementioning
confidence: 99%
“…Poor lithium-ion battery performance under cold climates is therefore studied [84,86,87] which can be summarised from four factors: 1) low conductivity of the electrolyte and solid electrolyte interface on the electrode surface [88,89]; 2) declined solid-state Li diffusivity [80,84]; 3) high polarisation of the graphite anode [76,90]; and 4) the sluggish kinetics and transport processes caused by increased charge-transfer resistance on the electrolyte-electrode interfaces [80,84]. Three contributing factors of a PHEV lithium-ion battery impact of low ambient temperature at -7°C and 0°C have been quantified [82].…”
Section: Sub-zero Temperature Performancementioning
confidence: 99%
“…Although the capacity increases as the operating temperature is raised, the degree of capacity fade also increases. On the other hand, poor performance is observed at low operating temperature [12,13]. In addition, excessive or uneven temperature rise in a system or pack reduces its lifecycle significantly [14].…”
Section: Introductionmentioning
confidence: 99%